A cembranoid from tobacco prevents the expression of nicotine-induced withdrawal behavior in planarian worms - Pagán, Oné R. (2009)
Using an adaptation of published behavioral protocols, we determined that acute exposure to the cholinergic compounds nicotine and carbamylcholine decreased planarian motility in a concentration-dependent manner. A tobacco cembranoid (1S,2E,4R,6R,7E,11E)-cembra-2,7,11-triene-4,6-diol (4R-cembranoid), also decreased planarian motility. Experiments in the presence of 1 μM 4R-cembranoid did increase the IC(50) for nicotine- but not carbamylcholine-induced decrease in planarian motility. When planarians were exposed for 24 h to either nicotine or carbamylcholine at concentrations near their respective IC(50) values and then transferred to plain media, nicotine-exposed, but not carbamylcholine- or cembranoid-exposed worms displayed withdrawal-like distress behaviors. In experiments where planarians were pre-exposed to 100 μM nicotine for 24 h in the presence of 1 μM 4R-cembranoid, the withdrawal-like effects were significantly reduced. These results indicate that the 4R-cembranoid might have valuable applications for tobacco abuse research. This experimental approach using planarians is useful for the initial screening of compounds relevant to drug abuse and dependence.